Critical notes on systematic of Pinophyta in Ukrainian flora (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
New data on some critical taxa of Pinophyta in Ukrainian flora are given and discussed with presenting identification keys. Next taxa are treated: Ephedra arborea Lag. – as synonym of E. distachya L., Pinus pallasiana Lamb. – as P. nigra J. F. Arnold subsp. pallasiana (Lamb.), P. pityusa Steven var. stankewiczii Sukacz. – as P. brutia Ten. var. pityusa (Steven) Silba.; P. sylvestris L. – as divided into three varieties: var. sylvestris, var. cretacea Kalen. ex Kom. and var. hamata Steven; P. mugо Turra – as divided into two subspecies: subsp. mugo and subsp. rotundata (Link) Janen. et H. Neumayer; Larix decidua Mill. – as divided into two varieties: var. decidua and var. polonica (Racib. ex Wóycicki) Ostenf. et Syrach; Juniperus oxycedrus L. replaced by J. deltoides R.P. Adams, J. communis L. – as divided into two varieties: var. communis and var. saxatilis Pall.; Platycladus orientalis (L.) Franco is given as naturalized in Ukraine for the first time.
Keywords: Pinophyta, systematic, Ukrainian flora.